Where next for monetary policy? Lessons from the financial crisis and the pandemic - Patrick Minford (Cardiff University, Cardiff Business School, 2023)
Monetary developments of recent decades began with much promise with inflation targeting by independent central banks; the financial crisis of 2007 ushered in a period of great monetary instability. There are lessons for a return to more stability. Central banks need to stabilize money supply growth. Fiscal policy should be coopted to a stabilization role to reduce interest rate instability, and particularly future risks of hitting the zero-interest rate bound. Budget discipline should be enforced by long run solvency rules, not by short run fiscal rules that in practice prevent the use of fiscal policy. Nor should the budget be burdened by monetary policy methods that transfer seigniorage to commercial banks.
Keywords: 330; Monetary policy; Fiscal policy; Financial crisis; Coronavirus; Impact analysis; USA; Great Britain; Eurozone; Geldpolitik; Finanzpolitik; Finanzkrise; Coronavirus; Wirkungsanalyse; USA; Großbritannien; Eurozone